Biomass-fuelled improved cookstove intervention to prevent household air pollution in Northwest Ethiopia: a cluster randomized controlled trial - Mesafint Molla Adane; Getu Degu Alene; Seid Tiku Mereta (Komiyama Printing Co. Ltd, 2021)
Abstract Background Household air pollution from biomass fuels burning in traditional cookstoves currently appeared as one of the most serious threats to public health with a recent burden estimate of 2.6 million premature deaths every year worldwide, ranking highest among environmental risk factors and one of the major risk factors of any type globally. Improved cookstove interventions have been widely practiced as potential solutions. However, studies on the effect of improved cookstove interventions are limited and heterogeneous which suggested the need for further research. Methods A cluster randomized controlled trial study was conducted to assess the effect of biomass-fuelled improved cookstove intervention on the concentration of household air pollution compared with the continuation of an open burning traditional cookstove. A total of 36 clusters were randomly allocated to both arms at a 1:1 ratio, and improved cookstove intervention was delivered to all households allocated into the treatment arm. All households in the included clusters were biomass fuel users and relatively homogenous in terms of basic socio-demographic and cooking-related characteristics. Household air pollution was determined by measuring the concentration of indoor fine particulate, and the effect of the intervention was estimated using the Generalized Estimating Equation. Results A total of 2031 household was enrolled in the study across 36 randomly selected clusters in both arms, among which data were obtained from a total of 1977 households for at least one follow-up visit which establishes the intention-to-treat population dataset for analysis. The improved cookstove intervention significantly reduces the concentration of household air pollution by about 343 μg/m3 (Ḃ = − 343, 95% CI − 350, − 336) compared to the traditional cookstove method. The overall reduction was found to be about 46% from the baseline value of 859 (95% CI 837-881) to 465 (95% CI 458-472) in the intervention arm compared to only about 5% reduction from 850 (95% CI 828-872) to 805 (95% CI 794-817) in the control arm. Conclusions The biomass-fuelled improved cookstove intervention significantly reduces the concentration of household air pollution compared to the traditional method. This suggests that the implementation of these cookstove technologies may be necessary to achieve household air pollution exposure reductions. Trial registration The trial project was retrospectively registered on August 2, 2018, at the clinical trials.gov registry database ( https://clinicaltrials.gov/ ) with the NCT03612362 registration identifier number.